Current Progress on the Genomics of Schistosomiasis for Drug Discovery and Diagnostics - Meghani, Nileshkumar; Lee, Beom-Jin; Amin, Hardik; Nili-Ahmadabadi, Behzad; Nagendran, Saraswathy (Infectious Disorders - Drug Targets, 2020)
For a number of decades, schistosomiasis has remained a public threat and an economic burden in a number of countries, directly impacting over 200 million people. The past 15 years have seen tremendous progress in the development of high-throughput methods for targeting or compound selection that are vital to early-stage schistosome drug discovery research. Genomewide approaches to analyze gene expression at the transcriptional and other -omic levels have helped immensely for gaining insight into the pathways and mechanisms involved in the schistosomiasis and it is expected to revolutionize the drug discovery as well as related diagnostics. This review discusses the most recent progress of pharmacology and genomics concerning schistosomiasis with a focus on drug discovery and diagnostic tools. It also provides chemical structural insights of promising targets along with available in vitro and/or in vivo data. Although significant research has been done to identify new molecules for the treatment and new methods for diagnosis, the necessity of new options for the sustainable control of schistosomiasis remains a great challenge.
Keywords: personalized medicine